(untitled) (Journal of Tikapur Multiple Campus, 2023)
Genetic variability is necessary for any crop breeding program to develop superior varieties. The objective was to estimate the genetic variability for growth and yield traits. The experiment was carried out at Baijanath-4, Banke district, Province no. 5 Nepal during June to November, 2019. Eleven rice genotypes were evaluated in a randomized complete block design with three replications. Days to flowering, days to maturity, panicle length, plant height, number of panicle per hill, number of tiller perhill, grain yield and thousand grain weights were found significant. Moreover, number of panicle perhill having high heritability (79%) have maximum genotypic coefficient of variation (29.03). Further, thousand grain weight, grain yield, plant height need to be considered as effective traits for breeding material selection. PB 1509 was declared superior genotype among aromatic genotype and also found as effective genotype with short height, more thousand grain weight, higher yield potential than compare to check HH1. Thus, the exploitation of PB1509 in further yield trial will contribute to National Rice Breeding Programs of Nepal.